Comparative analysis of fodder value of Sudanese herb varieties in the Karaganda region - Madiyeva, A.N. (Fundamental and Experimental Biology, 2022)
The article presents the results of an experiment on the cultivation of three varieties of Sudanese grass in the conditions of Karaganda city. Sudanese grass is a heat-loving valuable food crop with high drought resistance. It is cultivated to produce green feed,hay, silage. It is a rich source of vitamins, proteins, minerals. The results of field experiments showed that cryopreservation of Sudanese grass seeds had a positive effect on the productivity of the aboveground mass. Excessin terms of yield indicators for the “Novosibirsk 84” variety is 38.85 c/ha for raw weight and 58.80 c/hafor dry weight; for the “Nika” variety — by 23.55 and 41.25 c/ha, respectively; for the “Tugai” variety —8.55 and 8.55 c/ha, respectively. According to thefodder value analysis, all three varieties of Sudanese grass have good nutrition of aboveground organs. Varieties differ slightly in the accumulation of starch, sugar, raw protein, ash, carotene, calcium, and phosphorus. Preliminary data make it possible to distinguish the “Novosibirsk 84” variety with the maximum yield, and the “Tugai” variety with the maximum accumulation of elements of fodder value.